A Comparative Bibliometric Analysis and Visualization of Indian and South Korean Library and Information Science Research Publications During 2001–2020 - Kappi, Mallikarjun; Biradar, B S (International journal of knowledge content development & technology, 2022)
The paper aims to present a comparative analysis of scholarly research output in the fields of Library and Information Science (LIS) in India and South Korea.The Web of Science database was used to retrieve the bibliographic data of the Indian and South Korean LIS published documents during 2001–2020 and the indicators were included in the analysis: research productivity, publication-quality, most prolific authors, institutions and journals, “Annual Growth Rate (AGR)”, “Compound Annual Growth Rate (CAGR)”, “Relative Growth Rate (RGR)”, and “Doubling Time (DT)”. All types of documents such as articles, conference papers, book reviews, corrections, editorial materials, so on were included in the study. MS Excel, VOS viewer, and bibliometrix (R-tool) software were used for tabulation and mapping.The results show that South Korea placed the top in the overall output of LIS research publications during the last two decades. The Indian LIS research output, Annual Growth Rate (AGR), and Compound Annual Growth Rate (CAGR) were good compared to South Korean LIS publications. In addition, the South Korean LIS researchers’ output has increased rapidly in terms of publications, citations, average citations. Gangan Prathap (India), Seyoung Lee, and Heejin Lee (SK) are the most prolific authors; Indian Institute Technology, Delhi and Yonsei University, Seoul are the most prolific institutions; and the Scientometrics journal was the most preferred journal by the Indian and South Korean LIS researchers during the study period.The results of this study are useful to administrators, policymakers, and academics. In addition, the scope of this study might include looking at research published by LIS scholars in India and South Korea, as well as examining all types of academic publications.